IMPLEMENTASI KEBIJAKAN PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS DI KABUPATEN KAMPAR - Trisna Zakiyya; Hasim As'ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kampar Regency is a Regency that implements a policy of protection and empowerment of persons with disabilities. The protection and empowerment of persons with disabilities aims to realize the independence and welfare of persons with disabilities. Kampar Regency is the regency that has the highest number of persons with disabilities in Riau Province. With the large number of people with disabilities in Kampar District, there are still people with disabilities who have not received social assistance, at least people with disabilities who attend rehabilitation training and the limited accessibility provided by the government for persons with disabilities. The purpose of this study was to find out how the implementation of protection and empowerment of persons with disabilities in Kampar District and inhibiting factors of implementation. The theoretical concept used is the concept of Purwanto and Sulistyastuti's Implementation Theory (2015: 86). This research uses a qualitative method using purposive sampling technique. The results of this study indicate that the implementation of protection and empowerment policies for persons with disabilities in Kampar Regency has not been optimal in implementing policies for the protection and empowerment of persons with disabilities in Kampar Regency. Inhibiting the implementation of protection and empowerment policies for persons with disabilities in Kampar District is the lack of resources, the lack of responsive target groups and communication between implementing agencies and mindset of the target group’s family. Keywords: Policy Implementation, Protection and empowerment, Persons with disabilities